2019
DOI: 10.3847/2041-8213/ab263a
|View full text |Cite
|
Sign up to set email alerts
|

The Supersonic Project: Shining Light on SIGOs—A New Formation Channel for Globular Clusters

Abstract: Supersonically induced gas objects (SIGOs) with little to no dark matter component are predicted to exist in patches of the Universe with non-negligible relative velocity between baryons and the dark matter at the time of recombination. Using arepo hydrodynamic simulations we find that the gas densities inside these objects are high enough to allow stars to form. An estimate of the luminosity of the first star clusters formed within these SIGOs suggests that they may be observed at high redshift using future H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(89 citation statements)
references
References 91 publications
(115 reference statements)
4
84
1
Order By: Relevance
“…In the first class of models (e.g. Peebles 1984;Katz & Ricotti 2014;Trenti et al 2015;Chiou et al 2019) GC formation requires the special conditions of the early universe, forming before or during the epoch of reionization (z 6). In the second class (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the first class of models (e.g. Peebles 1984;Katz & Ricotti 2014;Trenti et al 2015;Chiou et al 2019) GC formation requires the special conditions of the early universe, forming before or during the epoch of reionization (z 6). In the second class (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This allows them to survive as independent, DM-depleted objects. Simulations suggest that these objects could potentially evolve into presentday globular clusters (Chiou et al 2019).…”
Section: Analytic Modelmentioning
confidence: 99%
“…These objects, known as supersonically induced gas objects (SIGOs), have since been found in follow-up simulations (Popa et al 2016;Chiou et al 2018Chiou et al , 2019Chiou et al , 2021. However, there are still many outstanding questions about these objects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view, which might seem obvious now, is in itself a change in thinking from earlier times. Numerous early approaches suggested that GC formation might be special in some way, connected with the early universe; examples include Peebles & Dicke (1968); Fall & Rees (1985); Murray & Lin (1992); Moore et al (2006); Chiou et al (2019). However, those semi-cosmological ideas encounter fundamental and probably insurmountable obstacles: for example, there is no special mass scale for GCs (much current evidence indicates that their initial mass distribution has a power-law form, and the present-day GC luminosity function with its lognormal shape has been produced instead by dynamical evolution and preferential removal of lower-mass clusters).…”
Section: Introductionmentioning
confidence: 99%